Application of the Actiphage® Assay to Detect Viable Mycobacterium avium subsp. paratuberculosis Cells in Fresh Sheep and Goat Milk and Previously Frozen Milk and In-Line Milk Filters - Beinhauerova, Monika; Slana, Iva (Frontiers in Veterinary Science, 2021)
Mycobacterium avium subsp. paratuberculosis (MAP) is a well-known causative agent of paratuberculosis, a chronic infectious granulomatous enteritis of ruminants contributing to significant economic losses worldwide. Current conventional diagnostic tools are far from being sufficient to manage and control this disease. Therefore, increased attention has been paid to alternative approaches including phage-based assays employing lytic bacteriophage D29 to detect MAP cells. The aim of the present study was to assess the applicability and efficiency of the recently developed phage-based kit termed Actiphage® combined with IS900 real-time PCR (qPCR) for rapid detection and quantification of viable MAP in milk samples. We demonstrated that Actiphage® in combination with IS900 qPCR allows for rapid and sensitive detection and identification of viable MAP in milk samples with a limit of detection of 1 MAP per 50 ml milk. Using this method, the presence of viable MAP cells was successfully determined in 30.77% of fresh goat, sheep and cow milk samples originating from paratuberculosis-affected herds. We further used Actiphage assay to define the time-lapse aspect of testing naturally contaminated milk and milk filters frozen for various lengths of time by phage-based techniques. Viable MAP was detected in 13.04% of frozen milk samples and 28.57% of frozen milk filters using Actiphage-qPCR. The results suggest the ability to detect viable MAP in these samples following freezing for more than one year. The obtained results support the views of the beneficial role of this technology in the control or monitoring of paratuberculosis.